Essays in Macroeconomics and Wealth Inequality - Cima, Simone (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2025)
This dissertation consists of three essays studying the dynamics of wealth inequality as it relates to different macroeconomic developments. In the three essays, I employ a range of different methods used in macroeconomics, and both empirical and theoretical frameworks. Each of the essays contributes a novel perspective, whether through the specific focus, or the use of data, to its respective literature. Chapter 1 studies how the shape of an economy's population distribution, or population pyramid, can affect rates of return and incomes. In turn, I observe how these developments can lead to unequal wealth accumulation journeys of cohorts of the population born at different points in time. Because older populations accumulate more wealth and have lower employment rates, young people in an ageing society face lower returns, and as a result accumulate wealth more slowly; at the same rates of savings, this implies lower standards of living at retirement for these cohorts compared to the cohorts who were of working age during population booms, leading to inter-generational inequality. I employ instrumental-variable fixed-effect panel regressions, using a unique parameterisation of the shape of the population distribution, and a number of back of the envelope calculations. Chapter 2 analyses the effect of a number of housing market policies on inequality in housing wealth, wealth, income and consumption, as well as homeownership. This is done by constructing a heterogeneous agent overlapping-generations model which features endogenous choice between renting and homeownership, and both a housing and a rental market. Within this framework, we study the effect of macroprudential policies, rental income taxation, the role of institutional investors in the housing market, supply side housing policies, and interest rates, as well as combinations thereof. We highlight a number of insights from this exercise, with sometimes unintuitive results, that can be of great value for policymakers. We also provide a solid framework for future work exploring the effects of the same policies with more complexities, as well as other policies. Chapter 3 estimates the differential effect of ECB monetary policy shocks on the wealth of euro area households across the wealth distribution. We employ panel local projections on newly published, quarterly distributional wealth data for the euro area, and identified monetary policy shocks. We find that the wealth levels and compositions of households at different positions in the wealth distribution respond differently. For instance, the net wealth, asset and debt levels of the bottom half decline significantly in response to a contractionary monetary policy shock, while the wealth of the top 10% of the distribution shows an almost opposite behaviour. We also highlight significant portfolio rebalancing across the distribution, and an asymmetry in the responses to contractionary versus expansionary shocks.
APPROVED
Keywords: Macroeconomics; Inequality; Wealth; Housing; Demographics; Monetary Policy